Protein-DNA Interactions Determine the Shapes of DNA Toroids Condensed in Virus Capsids - Leforestier, Amélie (The Biophysical Society, 2011)
DNA toroids that form inside the bacteriophage capsid present different shapes according to whether they are formed by the addition of spermine or polyethylene glycol to the bathing solution. Spermine-DNA toroids present a convex, faceted section with no or minor distortions of the DNA interstrand spacing with respect to those observed in the bulk, whereas polyethylene glycol-induced toroids are flattened to the capsid inner surface and show a crescent-like, nonconvex shape. By modeling the energetics of the DNA toroid using a free-energy functional composed of energy contributions related to the elasticity of the wound DNA, exposed surface DNA energy, and adhesion between the DNA and the capsid, we established that the crescent shape of the toroidal DNA section comes from attractive interactions between DNA and the capsid. Such attractive interactions seem to be specific to the PEG condensation process and are not observed in the case of spermine-induced DNA condensation.